A Friulian Landscape. Pasolini’s Heritage in Casarsa della Delizia Territory - Fabris, Luca Maria Francesco; Balzarotti, Riccardo Maria (Landscape Architecture and Art, 2024)
The paper highlights the potential for landscape and territorial enhancement in the Friulian locations associated with Pier Paolo Pasolini’s youth. By analysing Pasolini’s writings from his Friulian period and conducting archival research on materials and landscape development projects in the Casarsa area—many of which remain only partially realised—it is possible to outline trajectories for future valorisation efforts. These efforts aim to preserve and enhance a landscape that, despite its compromises, retains unique characteristics intrinsically tied to the cultural legacy of Pier Paolo Pasolini.